Governança de tecnologia da informação: uma análise no contexto da administração pública federal brasileira - Lemes, Jeferson Farias (2021)
The growing dependence of companies on information, and consequently on information technology (IT), demands an IT governance (ITG) capable of harmonizing the decisions about the administration and the use of these resources to reach the organizational objectives. The importance of ITG in private organizations has been the subject of recent studies, showing its qualities, benefits and impacts on organizational performance. However, there are significant differences in the scope of the public administration that is responsible for the management of resources in large volumes, higher than the budgets practiced for large projects in private companies. According to data from the Federal Budget Panel, from 2015 to 2018 IT investments in Brazil grew by an average of 6.8% per year, reaching a total of R$ 9.4 billion. However, in the last survey carried out by the Federal Audit Court (TCU), in 2018, it was identified that, among federal public organizations, 42% are in the initial stage of ITG, or do not even have any level. Given the influence of ITG on organizations, it is important to understand how the administration of financial resources for it takes place, especially in the context of the Federal Public Administration (APF), in which an important amount of public resources are reserved for this purpose. It is an applied research, with a descriptive objective and a qualitative and quantitative approach. In the qualitative phase, structural IT governance policies with wide coverage were analyzed, aimed at the organizations that make up the federal executive branch, the federal legislative branch, the judicial branch and the prosecution services. The quantitative phase reviews general budgetary aspects existing in its structures, in a selected sample, associating with other variables such as the iGovTI survey and the staff of civil servants. The results obtained indicate that the consolidation of IT expenses in the public administration establishes a scenario for the formalization of the ITG, with structural policies in this area still evolving. Despite this, the results reveal a situation of inequality between the branches of the government in terms of the structuring policies themselves, mainly involving guidelines related to human behavior, a factor that may be associated with the low levels of iGovTI in the APF, already disclosed by TCU in 2018. The study also showed that the executive branch is at a lower level than the others, despite receiving the largest amounts of resources, in absolute terms, which had steady growth in the period under investigation, influencing the federal budget as a whole. No relationship was identified between the budgetary aspects and the ITG levels indicated by the iGovTI assessment, a disconnect that may be related to the lack of action by the State in terms of its valuation and the need to improve the assessment instrument. In a context in which IT increasingly assumes the condition of a strategic element, it was possible to identify that it is still necessary to expand research on the use of IT in public organizations.